Orbital Energy and Spin Flows in a Strong Focus of Laser Light - Victor V. Kotlyar; Anton G. Nalimov; Sergey S. Stafeev; Alexey A. Kovalev; Alexey P. Porfirev (IEEE Photonics Journal, 2020)
In this work, we derive analytical relations for all projections of the orbital energy flow and spin flow in the focal plane of a strongly focused left-hand circularly polarized Gaussian beam, also calculating a torque exerted upon a dielectric ellipsoidal microparticle in the focus of the beam and discussing results of an experiment on rotating the microparticle around its center of mass. The on-axis projection of the torque exerted upon the microparticle is found to be negative, i.e., directed oppositely to the beam propagation axis. Such a torque is supposed to induce a clockwise rotation of a non-absorbing dielectric particle around its center of mass. We have been demonstrated that a reverse energy flow occurs in the light field regions where the longitudinal projection of the spin flow is negative and larger in magnitude than the longitudinal projection of the orbital energy flow, which is always positive.